Cannibal capitalism : how our system is devouring democracy, care, and the planet - and what we can do about it - Fraser, Nancy (London: Verso, 2022)
Capital is currently cannibalizing every sphere of life-guzzling wealth from nature and racialized populations, sucking up our ability to care for each other, and gutting the practice of politics. In this tightly argued and urgent volume, leading Marxist feminist theorist Nancy Fraser charts the voracious appetite of capital, tracking it from crisis point to crisis point, from ecological devastation to the collapse of democracy, from racial violence to the devaluing of care work. These crisis points all come to a head in Covid-19, which Fraser argues can help us envision the resistance we need to end the feeding frenzy. What we need, she argues, is a wide-ranging socialist movement that can recognize the rapaciousness of capital - and starve it to death.
Includes bibliographical references (pages 167-180) and index.
Keywords: Capitalism; Socialism